2011
DOI: 10.1056/nejmsa1102519
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Health Records and Quality of Diabetes Care

Abstract: These findings support the premise that federal policies encouraging the meaningful use of EHRs may improve the quality of care across insurance types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
183
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(192 citation statements)
references
References 19 publications
6
183
2
1
Order By: Relevance
“…4 Furthermore, certain MU functionalities such as CPOE, electronic prescribing and clinical decision support have been associated with improvements in care. 2,[23][24][25][26][27][28][29][30] However, the full clinical benefits of MU have yet to be empirically evaluated and warrant future research. Although adoption of many functionalities varied by specialty, adoption of several functionalities associated with e-prescribing significantly increased between 2009 and 2011 across both primary care physicians and specialists.…”
Section: %)mentioning
confidence: 99%
“…4 Furthermore, certain MU functionalities such as CPOE, electronic prescribing and clinical decision support have been associated with improvements in care. 2,[23][24][25][26][27][28][29][30] However, the full clinical benefits of MU have yet to be empirically evaluated and warrant future research. Although adoption of many functionalities varied by specialty, adoption of several functionalities associated with e-prescribing significantly increased between 2009 and 2011 across both primary care physicians and specialists.…”
Section: %)mentioning
confidence: 99%
“…Several evidence reviews have identified interventions with modest effects in promoting both overall and condition-specific medication adherence. [11][12][13][14][15][16] Given the complex, multifactorial cause of medication non-adherence, interventions can be similarly multifactorial and multi-level. In this paper we focus on the physician-patient level to furnish providers with a guide to applying adherence research in the clinical encounter.…”
mentioning
confidence: 99%
“…The addition of electronic health records (EHRs) to ongoing quality improvement (QI) efforts has been shown to improve chronic care in large health care organizations [6,7] and in an urban QI collaborative [8]. However, few data document the effects of onsite practice facilitation services that incorporate both QI and the implementation of certified EHRs in small primary care practices, particularly those in rural areas.…”
mentioning
confidence: 99%